Industrial transfer policy in China: Migration and development - Michiel Gerritse; Zhiling Wang; Frank van Oort (Tinbergen Institute, 2024)
China's Industrial Transfer Policy (ITP) is a novel place-based development policy of unprecedented scale. The policy targets a set of inland cities aiming to i) grow them in size and ii) restructure them into manufacturing hubs. These cities would eventually relieve pressure in China's coastal manufacturing hubs. We use a detailed migrant survey to estimate the impact of ITP on targeted cities by matching cities on policy assignment propensities. The ITP status led to a rapid but short-lived growth of migrant inflows up to 60%, representing 2 to 7 million internal migrations. Migrants in manufacturing and from coastal origins show stronger migration and wage responses. However, high skilled migrants respond less elastically, and migrant employment in manufacturing is offset by the exit of native workers. Additionally, manufacturing industries in targeted cities show no development in terms of output, pollution or production strategies. The ITP expands the population of targeted cities, but the evidence for a restructuring of the cities is weak.
Keywords: R58; H50; O20; P25; J38; 330; migration; urbanization; development; wage; place-based policy; China